Validation of Educational Robotic-Based Vector Learning Module Using a Structured Inquiry Model to Improve Students' Computational Thinking Skills - Sabilah Hairun Anis; Wawan Kurniawan; Cicyn Riantoni; Hebat Shidow Falah (Edumaspul: Jurnal Pendidikan, 2025)
The problem that occurs in research schools is that students have difficulty in visualizing vector material with real context. After conducting the analysis, the solution provided to the above problem is in the form of robotic educational media. The use of educational robotics is expected to help students understand the vector material produced from the visualization of robot movements. This development aims to produce a product in the form of an educational robotic-based learning module using a structured inquiry model to improve students' computational thinking skills. The products that have been produced will be tested for validity by material experts and media experts. The development model used in this study is the ADDIE model which has only reached the development stage. The subjects of the study are physics teachers, material experts, and media experts. The data analysis technique used during the interview is spiral. Meanwhile, data from material experts and media experts used quantitative descriptive analysis. Based on the data of the validation results that have been obtained from the first subject matter expert is 78.27% with fairly valid criteria. The second material expert gave a score of 96.53 with very valid criteria and media experts got a validation score of 92.83% with very valid criteria. Based on the results of the validation above, the educational robotics-based vector learning module uses a structured inquiry model to improve computational thinking skills that are suitable for use.